Microstructural evolution and mechanical properties of diffusion bonding WC-Co cemented carbide to steel using Co and composite Ni/Co interlayers. (February 2022) - Li, Shiwei; Li, Zhaoxi; Chen, Yipeng; Zu, Yundi; Xiong, Jiangtao; Zhang, Fusheng; Li, Jinglong
Abstract: This study focuses on diffusion bonding of WC-Co cemented carbide to a steel using Co and composite Ni/Co interlayers. The typical microstructure and microstructural evolution with variable bonding temperatures were investigated, and mechanical properties of the joint were evaluated. The results illustrated that increasing temperature promoted interdiffusion of interfacial atoms, leading to the elimination of interfacial voids and the enhancement of Fe-Co-Cr interdiffusion zone on steel side. As the temperature increased, so did the thickness of Co6 W6 C formed near the WC-Co substrate (using Co interlayer). On the other hand, the Co6 W6 C was inhibited due to the addition of Ni foil, and replaced by the WC and (Ni, Co) solid solution resulting in satisfactory shear strength of the diffusion-bonded joint, where referring to using composite Ni/Co interlayer. The maximum shear strength of 418 MPa was achieved when the joint was diffusion-bonded at 1100 °C for 60 min using composite Ni/Co interlayer. In addition, ductile fracture occurred in the joint indicating propagation of cracks in the Ni-Co interdiffusion zone, and passing through the WC-Co substrate. Added up, this study provided experimental support for reliable joining cemented carbides to Fe- or Co-based alloys. Highlights: The diffusion bonding of WC-Co to a steel was achieved using Co and composite Ni/Co interlayers. Increase of bonding temperature contributed to the elimination of interfacial micro-voids, and promoted the formation of inter-diffusion zones. As the temperature increased, so did the thickness of Co6 W6 C. The Co6 W6 C was inhibited due to the addition of Ni, and replaced by the WC and (Ni, Co) solid solution.